Health-Related Quality of Life in Italian Adolescents During Covid-19 Outbreak - Mastorci, Francesca; Piaggi, Paolo; Doveri, Cristina; Trivellini, Gabriele; Casu, Anselmo; Pozzi, Marta; Vassalle, Cristina; Pingitore, Alessandro (Frontiers in Pediatrics, 2021)
COVID-19 outbreak represented an experience of social isolation potentially leading to changes in health quality of life. Aim of this study was to investigate health-related quality of life during quarantine in early adolescents. Data were collected in 1289 adolescents (mean age 12.5, male 622), at the beginning of school year (September 2019, Standard Condition, SC) as part of the AVATAR project and during the phase 1 of Italian lockdown (mid-late April 2020) (COVID-19 Quarantine, CQ) using online questionnaire. In CQ period, with respect to SC, adolescents showed lower perception in psychological (p=0.001), physical well-being (p=0.001), mood/Emotion (p=0.008), autonomy (p=0.001), and financial resources (p=0.018) dimensions. Relationship with family (p=0.021) and peers (p=0.001) were reduced, as well as the perception of bullying (p=0.001). In lifestyle, adolescents developed higher adherence to the Mediterranean diet (p=0.001). Adolescents living in the village had greater reduction in both autonomy (p=0.002) and peer relationships (p=0.002). Moreover, physical well-being perception was lower for those living in the city instead of countryside (p=0.03), in an apartment instead of detached house (p=0.002), in those who did not have green space (p=0.001). Gender effect emerged for psychological (p=0.007) and physical well-being (p=0.001), mood/emotion (p=0.001), and self-perception (p=0.001). The study showed that health-related quality of life during quarantine is changed in its psychosocial dimensions, from mood, self-esteem to social relationships, helping to define educational policies at multiple points in the promotion process of health.